Evaluating the usability of a co-designed interactive web application for cardiac rehabilitation. (2nd July 2022) - Nesbitt, K; Beleigoli, A; Champion, S; Gebremichael, L; Jacob, A; Du, H; Hendriks, J; Tirimacco, R; Clark, R A
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Novartis Background/significance: The rapid development of information technology is driving the evolution of choices of modes of delivery of healthcare services. The internet is an extremely powerful tool for accessing information, and communication. However, involvement of patients in the assessment of such an intervention is crucial, and can be achieved through a person-centred approach, utilising a co-design process with the aim to increase intervention usability. Purpose: To assess the usability of the Country Access to Cardiac Health (CATCH) Web, an interactive web application for cardiac rehabilitation (CR), co-designed with rural and remote Australians, following the co-design development phase. Methods: The User Experience (UX) Design framework was used to co-design the web portal with CR patients through two rounds of six co-design workshops pre (n=39), and post (n=35). Participants and family members living in rural and remote areas of Australia were invited to participate based on their eligibility for CR as outlined by the National Heart Foundation of Australia. As part of the UX Design Framework the System Usability Scale (SUS) was used to measure objective feedback from participants on the website design. The SUS assesses the three core components of a products usability: effectiveness, efficiency and satisfaction using a 10 question Likert scale. Mean scores were compared between the two rounds of workshops using an independent T-Test. The mean SUS score is categorised into poor to moderate (<68), good (68-80.3) and excellent (>=80.3) and categories were compared between the two rounds of workshops through Chi-Square tests. Results: The 35 participants in the usability workshops had a mean age of 68.6 (SD 11.2) years and 16 (47%) were female (Table 1). The majority had experienced a myocardial infarction (15, 42.8%) and had hyperlipidemia (17, 50%), heart failure (15, 44%), hypertension (14, 41%), and Type II diabetes (7, 21%). Of these participants 20 (59%) used a smart phone, 18 (58%) had access to the National Broadband Network and 20 (59%) engaged with Facebook. From the first to the second round of workshops, there was an improvement in the mean SUS scores from 66.7 (SD16.8) to 73.6 (SD 21.0); p=0.26. The proportion of participants rating it as good or excellent increased from 48.7 to 65.8%; p=0.11 (Figure1). Conclusion: The usability testing of the interactive CATCH web application showed an improvement in the SUS rating from poor to moderate in the co-design development phase to good or excellent by most of the participants in the usability testing phase. Usability is closely related to engagement with a digital health intervention. Upcoming evaluation of this intervention will report on clinical outcomes.